Bufei Huoxue capsule attenuates COPD-related inflammation and regulates intestinal microflora, metabolites - Li, Yuanyuan; Chen, Jiali; Xing, Yue; Wang, Jian; Liang, Qiuling; Zeng, Jiamin; Wang, Siyi; Yang, Qiong; Lu, Jianing; Hu, Jieying; Lu, Wenju (Frontiers in Pharmacology, 2024)
Background: Bufei Huoxue capsule (BFHX) is widely used for the clinical treatment of chronic obstruction pulmonary disease (COPD) in China.Objectives: the effect on COPD and underlying mechanism of BFHX remains to be explored.The process and methods: In this study, we established a COPD mouse model through cigarette smoke (CS) exposure in combination with lipopolysaccharide (LPS) intratracheal instillation.Subsequently, BFHX was orally administrated to the COPD mice, and their pulmonary function, lung pathology, and lung inflammation, including bronchoalveolar lavage fluid (BALF) cell count and classification and cytokines, were analyzed. In addition, the anti-oxidative stress ability of BFHX was detected by western blotting, and the bacterial diversity, abundance, and fecal microbiome were examined by 16S rRNA sequencing technology.Outcome: BFHX was shown to improve pulmonary function, suppress lung inflammation, decrease emphysema, and increase anti-oxidative stress, while 16S rRNA sequencing indicated that BFHX can dynamically regulate the diversity, composition, and distribution of the intestinal flora microbiome and regulate the lysine degradation and phenylalanine metabolism of COPD mice. These results highlight another treatment option for COPD and provide insights into the mechanism of BFHX.